The effect of au-seeded thickness to the gas sensing properties of ZnO nanostructures obtained by mist-atomization on heated substrates / Nurul Afaah Abdullah … [et al.] - Abdullah, Nurul Afaah; Mohd Asib, Nur Amierah; Abd Aziz, Noor Aadila; Khusaimi, Zuraida; Mahmood, Mohamad Rusop (Research Innovation Business Unit, 2014)
Zinc oxide (ZnO) is an n-type semiconductor with a wide direct band-gap of 3.37 eV at room temperature. ZnO exhibit high-transparency in the visible region, near-UV emission, magnetic, piezo-electric, high-conductivity [1] and piezoelectric dual properties [2]. Its properties can be adjusted by controlling size and morphology [3]. Wide application of ZnO has been found such as varistor, gas sensor [4], UV photoconductive sensor [5], high-efficient green phosphor, field emission displays and solar cell [3]. ZnO also display a strong bonding energy of 60 meV, much larger than gallium nitride (GaN, 25 meV). Zinc oxide (ZnO) nanostructure is very responsive and sensitive towards the synthesis methods. Low-dimensional ZnO nanostructures like nanowires, nanorods, and nanotubes may be selectively formed to be considered for usage in new application areas and developing existing applications in nanoelectronics and nanophotonics due to their efficient transport of electrons and excitons [6], large surfaceto-volume ratio and quantum confinement effects [7]. The synthesis methods often face limitations in terms of sample uniformity, substrate selection, and low product yield. On the contrary, approaches using solution-based are attractive because of the low temperature growth, potential for scaling up and much easier operation in fabricating high-density ZnO arrays [8], however vapor method give better results in synthesizing ZnO nanostructures in room temperature (RT). In this paper, we focus on the synthesis of ZnO nanostructures were obtained by a simple and low-cost synthesis method; mist-atomization. The starting materials for this synthesizing method are zinc nitrate hexahydrate as precursor solution and hexamethylenetetramine (HMTA) as the stabiliser. ZnO nanostructures were deposited by mist-atomization with applied heat from substrates’ downside. The glass substrates first seeded with gold (Au) with 0, 6 and 12 nm thickness. The gas sensing properties of the samples were examined by UV-Vis (UV-Visible) spectroscopy, Field Emission Scanning Electron Microscope (FESEM) micrograph and I-V (Current-Voltage) measurement. FESEM micrographs show the different morphology of ZnO nanostructures obtained on different Au-seeded thickness glass substrate. There is improvement in UV region analysed from ZnO nanostructure growth on 6 nm Au-seeded glasses. I-V measurements also show some improvement in gas sensing properties of ZnO on different Au-seeded glass substrate. The optical, morphological properties and I-V (IV) measurement of sprayed ZnO nanostructures growth on different Au-seeded glass substrate largely depend on the substrates temperature during spraying the zinc acetate solution and on the Au-seeded glass substrates.